University students’ perception, evaluation, and spaces of distance learning during the COVID-19 pandemic in Austria: what can we learn for post-pandemic educational futures? - Bork-Hüffer, Tabea; Kulcar, Vanessa; Brielmair, Ferdinand; Markl, Andrea; Immer, Daniel Marian; Juen, Barbara; Walter, Maria Hildegard; Kaufmann, Katja (Sustainability, 2021)
The COVID-19 pandemic caught societies worldwide unprepared in 2020. In Austria, after a lockdown was decreed on 16 March 2020, educational institutions had to switch to a patched-up distance learning approach, which has been largely maintained to date. This article delivers empirical insights from an interdisciplinary mixed-methods research study that investigated university students’ perceptions of and experiences with distance learning as well as their educational (home) spaces during the pandemic in Innsbruck, Austria. It combines results from a quantitative survey conducted with 2742 students in early 2021 with a qualitative multi-method and longitudinal research study that accompanied 98 students throughout four data-collection phases in 2020. Results show a significant improvement since spring 2020 with both teachers and learners adjusting to the distance learning formats and the use of digital tools, yet students urgently desired a return to face-to-face teaching and university life, particularly for its social benefits. Strikingly, more than half of the participants wanted to maintain the option of overall distance education after the pandemic. Based on the perspectives of students, it is appropriate to demand significant changes in post-pandemic education adapted to the era of the post-digital, for which this article gives short-term as well as medium-term recommendations.